2016
DOI: 10.1159/000445292
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Continuation of Contraceptive Methods Immediate Postabortion

Abstract: Background/Aims: Providing preabortion contraceptive counseling for the method of contraception may reduce the incidence of repeat abortions. This study aimed to compare the acceptance and continuation rates of intrauterine devices (IUDs), combined oral contraceptives (COCs), and condom use after abortion in women who received preabortion contraceptive counseling. Methods: Women seeking a first-trimester abortion prospectively received preabortion contraceptive counseling and the choice of method of contracept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…1 ). A total of 16 studies met inclusion criteria: 9 focused on medical abortion and 7 on surgical abortion ( Tables 2 and 3 ) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . We did not identify any studies of hormonal contraception use following spontaneous or septic abortion that met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). A total of 16 studies met inclusion criteria: 9 focused on medical abortion and 7 on surgical abortion ( Tables 2 and 3 ) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . We did not identify any studies of hormonal contraception use following spontaneous or septic abortion that met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…A second cohort study included 705 people who had a surgical abortion at 6 to 10 weeks gestation and initiated COC ( n = 230), Cu-IUD ( n = 240), or condoms ( n = 235) on the day of the surgical abortion [30] . The COC group exhibited shorter duration of bleeding (COC: 5 days [2-7], Cu-IUD: 7 days [2-10], condom: 5.5 days [3][4][5][6][7][8]; p = 0.041) on telephone follow-up at 1, 3, and 6 months.…”
Section: Hormonal Contraception Vs Nonhormonal or No Contraceptionmentioning
confidence: 99%
“…Celen et al [6] found continuation rate of 76.3% at 12 months after post placental insertion of Copper T 380 IUD. Continuation rates for immediate post-abortion insertion of copper IUD after 6 months of use show the data at 77.9% [7] and 64.2% [8]. While a multicentre randomized clinical trial showed one-year continuation rate for Copper IUD was 76.3% [9] for interval insertion.…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast the study by Shu-Ping Hou of 2015 concluded that the use of COCs in post abortion period had low continuation rates despite the pre-abortion contraceptive counselling. 11 The satisfaction level depicting the acceptability was 93 (77.5%) and 78 (65%) in ormeloxifene and COC respectively with statistically significant difference [p=78 (65%)]. Continuation rates decreased with time for both the groups.…”
Section: Continuation Ratesmentioning
confidence: 92%